Pandangan Ibnu Qayyim al-Jauziyah tentang al-Ba’sâ’, al-Dharrâ’, dan al-Zilzâl; Kajian Tafsir Metafora Al-Qur’an - Abdul Basid (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2014)
In the Al-Qur’an there are texts that are metaphors or amthâl, to understand it in need of a special method. al-tamthîl al-qas?s?âs?î (depiction novelisitik) is one method that in the mentioned by Ibn Qayyim al-Jauziyah. This method understand a verse by the state earlier peoples as subjects (ibrâh) due to similarity of circumstances or events therein. Al-ba’sâ’, al-d?arrâ’ and al-zilzâl equally meaningful trials. By this method, three words are the laws that apply to all people, and not confined only to Muslims only. So that the filtration and separation of the believers who wait with impatient is dependent on how to deal with the ordeal.